Exploration and Reintroduction of Orchid on the West Slope of Mount Lawu: Conservation Studies PT Pertamina Aviation Fuel Terminal Adi Sumarmo - Soraya, Nova Dewi; Bagas Cesar Bastomi; Julia Rizki Jumas; Zaenal Abidin; Harya Ramadanu (Prospect Publishing, 2024)
This study aimed to inventory the taxonomic diversity of Orchidaceae on the western slopes of Mount Lawu, a conservation area managed by PT Pertamina Aviation Fuel Terminal Adi Sumarmo. Through exploratory methods, 51 orchid taxa were identified with a total of 230 individuals. The Eria, Dendrobium, and Liparis genera dominated the species composition, with their distribution influenced by microhabitat characteristics. The significant presence of epiphytic species suggests a healthy forest canopy. Vegetative propagation efforts through tissue culture were successfully conducted on five selected species: Eria sp, Liparis sp, Dendrobium sp, Malaxidinae sp, and Vanda tricolor, with Dendrobium sp demonstrating the highest potential for vegetative propagation (26%). These findings open avenues for reintroduction programs of rare species into their natural habitats. A conservation status assessment revealed that most species are not yet listed in the IUCN Red List, emphasizing the urgent need for further research and more intensive conservation efforts. Therefore, this study recommends the implementation of integrated in-situ and ex-situ conservation strategies to ensure the sustainability of orchid diversity within the Mount Lawu conservation area.